2021
DOI: 10.4103/jasi.jasi_206_20
|View full text |Cite
|
Sign up to set email alerts
|

Sheath of Distal Tendon of Semimembranosus Muscle and it's Functional Significance

Abstract: Introduction: Semimembranosus (SM) muscle is important in maintaining the stability of knee joint, and the distal end of it's tendon is not only complex but has been described differently in the available literature, which is quite perplexing. How a muscle with such divergent attachments can efficiently perform it's functions? Hence a detailed study of the distal semimembranosus tendon unit was undertaken. Material and Methods: One hundred lower limbs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…We also observed that the origin of the MCN was highly variable. The MCN has been reported to branch inside the TT [20,23,27,30,34,41,52,62,77], or proximal to it [18,20,57,73,77].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We also observed that the origin of the MCN was highly variable. The MCN has been reported to branch inside the TT [20,23,27,30,34,41,52,62,77], or proximal to it [18,20,57,73,77].…”
Section: Resultsmentioning
confidence: 99%
“…MPN and LPN) has also been noted if the origin of the MCN is very high or low [20,21,30,75]. Authors have classified the bifurcation of TN into five types, of which type I (bifurcation proximal to the MCA but in the TT) is most frequent [7,15,32,35,36,41,52,54,71,77,78]. Some have also measured the distance of the bifurcation from the MCA and found it usually to be within 2 cm proximal to the axis [7,18,52,77].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 ). Correct positioning was determined by noting a hallux reaction (plantar flexion of the big toe or, rarely, fanning of the fingers) [ 14 15 16 17 18 ]. The stimulation protocol was applied at a continuous mode of 20 Hz and a pulse width of 200 µs [ 7 9 13 ].…”
Section: Methodsmentioning
confidence: 99%